Characterization and analysis of high‐entropy boride ceramics sintered at low temperature. Issue 5 (13th January 2023) - Zou, Qin; Gu, Haotian; Li, Yanguo; Li, Zhang; Liang, Pengjie; Luo, Yongan
Abstract: Multicomponent transition metal boride composite–sintered bodies were prepared by spark plasma sintering, and the composite sintered bodies prepared at different sintering temperatures (1500–1900°C) were characterized. The experimental results showed that several other compounds diffused into the TiB x phase at lower sintering temperatures under the combined effect of temperature and pressure due to the nonstoichiometric ratio of TiB1.5 vacancies. When the temperature reached 1900°C, only the hexagonal phase remained. With the continuous increase of sintering temperature, the Vickers hardness and fracture toughness of the sintered bodies had a trend of increasing first and then decreasing, due to the continuous reduction of the porosity of the cross section of the sintered bodies and the growth of the grain size. The Vickers hardness and fracture toughness of sintered body obtained at 1800°C are the best, which are 24.4 ± 1.8 GPa and 5.9 ± 0.2 MPa m 1/2 . At 1900°C, the sintered body was a single‐phase hexagonal high‐entropy diboride. Its Vickers hardness and fracture toughness were 21.9 ± 1.5 GPa and 5.4 ± 0.2 MPa m 1/2, respectively; it showed a clear downward trend.